COST OF ILLNESS ANALYSIS: TYPES, METHODOLOGY, RUSSIAN SPECIFICS - R. I. Yagudina; I. Yu. Zinchuk; M. M. Litvinenko (Фармакоэкономика, 2015)
Cost of illness is one of the basic methods of pharmacoeconomical estimation and in substance consists in calculation of the expenses connected any given disease, without notice of effectiveness of therapy. Cost of illness analysis is a useful tool for effective planning of distribution of economical recourses of public health services at all levels of management for various diseases. Despite of seeming to the nonprofessional in this sphere simplicity of carrying out of the cost of illness researches, the methodology of the given analysis represents difficult structure of consecutive actions, from a choice and observance of which the final results depends, and the choice of a source of the data often causes difficulties